Polymerization Shrinkage and Push-out Bond Strength of Different Composite Resins for Sealing the Screw-access Hole on Implant-supported Crowns - Tribst, João Paulo Mendes [UNESP]; Piva, Amanda Maria de Oliveira Dal [UNESP]; Gonçalves, Natália Ines [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Bottino, Marco Antonio [UNESP]; Kleverlaan, Cornelis Johannes (My University, 2020)
Purpose: To evaluate the effect of composite resin polymerization shrinkage stress on the stress distribution in the implant-supported crown-access hole, and on the bond strength between the ceramic and composite resin. Materials and Methods: A 3D model of a ceramic crown, in which the access hole was filled with composite resin (conventional or bulk-fill), was used to evaluate the stress distribution in the access hole using finite element analysis. The contacts were considered bonded and the polymerization shrinkage was simulated based on the coefficient of linear thermal expansion of each resin. The push-out test (1 mm/min, 100 kgf) was performed on perforated lithium disilicate samples filled with conventional or bulk-fill resins to validate the stress data of the bond strength. One-way ANOVA and Tukey's test were used to analyze the bond strength data, with α set at 5%. Results: Conventional resin showed the worst stress distribution and highest displacement values, von Mises stress, maximum principal strain, maximum principal stress, and maximum shear stress vs the bulk-fill resin. Statistically significantly greater bond strength was observed for bulk-fill (13.40 ± 5.59 MPa) than the conventional resin (8.70 ± 3.02 MPa). Conclusion: Comparing both materials tested in the present study, the use of bulk-fill composite resin to seal the screw-access hole is suggested to reduce the stress concentration and increase bond strength to the ceramic crown.
Keywords: composite resins; finite element analysis; incremental technique; polymerization